Apostasy in Islam: By Taha Jabir Alalwani (London: IIIT, 2011. 157 pages.) (American Journal of Islam and Society, 2013)
This lucid and concise book is an important and timely contribution in lightof current intra-Muslim political rivalries that find their fueling justificationsin the domain of “excommunication” and mutual accusations of disbeliefand apostasy (takfīr). This situation has caused Alalwani, the author of this“treatise,” to delve into the controversies and subtleties of this sensitive andmanipulation-laden issue. He attempts, both scripturally and logically, to clarifyits various aspects and challenge the conventional and traditional approachesto it, which have been obscured by the historical weight of dogmaand power politics (pp. 19-20, 129).Alalwani’s contends that there is no explicitly stated evidence, whetherfrom the Qur’an or the Prophet’s Sunnah, that mandates the death penalty formerely changing one’s religion, as long as doing so is not accompanied or associatedwith another criminal act. He highlights that when stipulating that anapostate should be killed, the jurists were in fact dealing with “compound”crimes that involved, in addition to apostasy, other political, legal, and socialdimensions (p. 1). He proceeds to make his point by providing evidence fromthe Qur’an and the Sunnah while casting doubt on the authenticity or consistencyof much of what the fuqahā’ (jurists and scholars) narrated later on andattributed to the Prophet or his Companions. His chosen method combinesphilosophical, analytical, inductive, and historical approaches along with Islamictextual sciences and fields of knowledge (p. 3). He focuses on cases inwhich an individual changes his/her faith without engaging in hostile or criminalactivities against the Muslim community, which otherwise would elevatethe case to one of security threat or treason (p. 4).The study comprises six chapters. The first two deal with whether apostasyis a capital crime and with the Qur’anic depiction of what apostasy means.Alalwani points out that despite unleashing the “sword of consensus” regardingthe death penalty for this event, in fact there is no such consensus, for no ...